Al-Dur Al-Farīd Kiai Abul Fadhol Senori, Karya Terbesar Ilmu Kalam Ulama Nusantara - Cholil, Abdul Munim (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The kalam science is considered an Islamic science that has succeeded in becoming the hallmark of Islam. Even in Orientalist literature it receives special attention, as a special approach too. In al-Dur al-Farīd contains the core themes of kalam science by following the flow of the verses of Al-Laqqani's poetry, the author is also sensitive to modernity and even corresponded with Rashid Ridha. Meanwhile, this can be considered as the greatest work of Indonesian kalam science. This research will provide important information that there are Indonesian ulama whose expertise is on par with world ulama. This study will use Husserl's phenomenological approach, so that we can approach Senori's intentionality and consciousness more clearly.